Pengaruh Kualitas Produk, Harga, Promosi Terhadap Loyalitas Pelanggan Dalam Industri Fashion (Studi Kasus Pada Konsumen Di Toko Thrifshop SECONDBARKLEY) - Maulana, Muhamad Yusriel; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Changes and developments in current market conditions have had a big influence on the strategies that must be determined by companies in maintaining product quality, pricing, and promotion/marketing strategies for the products they will offer, so that the business can run as they expect, and Feedback from all these activities is to get regular customers who have visited their shop/outlet. This research aims to find out the influence of product quality, price, promotions on customer loyalty. The type of research used in this research is quantitative with a data collection method in the form of distributing questionnaires to 90 respondents, namely consumers at the SEONDBARKLEY thrifshop shop in Malang who will and have purchased second hand clothing products. Then the data obtained was processed using the SPSS computer program. The variable used in this research is Customer Loyalty (dependent variable), while the independent variables are Product Quality, Price and Promotion. This research has met the requirements for validity and reliability. The data analysis used in this research is classical assumption testing, multiple linear regression, hypothesis testing, and analysis of the coefficient of determination. The results of this research conclude that the variables Product Quality, Price, Promotion have a significant effect on Customer Loyalty, for secondbarkley thrifshop owners it is best to consider adjusting prices to the needs of the community in current conditions. Keywords: Product Quality, Price, Promotion, and Customer Loyalty